Associations between patient characteristics and five-year trajectories of anticholinergic drug burden in older adults in German primary care: a prospective observational cohort study - Tajdar, Daniel; Westphal, Juliane; Lühmann, Dagmar; Krüger, Caroline; Langebrake, Claudia; Bickel, Horst; Fuchs, Angela; Gensichen, Jochen; König, Hans-Helmut; Maier, Wolfgang; Mergenthal, Karola; Riedel-Heller, Steffi G.; et al. (BMJ open, 2025)
Objectives To investigate the change in anticholinergic burden over a 5 year period in relation to the health characteristics of older adults. - Study design Using data from the MultiCare Cohort Study (2008-2013), a prospective observational cohort study based on patient data from 158 general practices - Setting Primary care in Germany. - Participants 3189 multimorbid adults aged 65 to 85 years - Primary and secondary outcome measures The primary outcome was the change in the anticholinergic burden score (ACB) over a 5 year period. The ACB was defined as the dependent variable and was calculated by including all anticholinergic drugs prescribed to participants during the study period. Independent variables included age, sex, education (according to CASMIN), depressiveness (GDS), cognitive function (LDST), quality of life (EQ5D-3L) and the number of diseases weighted by severity. We performed multilevel mixed-effects multivariable linear regression analyses. - Results A total of 7068 observations were analysed during three follow-ups. The mean age of the participants was 74.4±5.2 years and 59.3% were female. The mean ACB score was 1.5±1.7 at baseline and did not change significantly over time. In contrast, a higher severity-weighted number of diseases (coefficient: 0.08, 95% CI: 0.05/0.10, p<0.001), a higher number of depressive symptoms (0.04, 0.004/0.08, p=0.030), poorer cognitive function (−0.03 to -0.06/−0.001, p=0.044) and poorer health-related quality of life (−0.05 to -0.08/−0.01, p=0.006) were associated with an increasing ACB score over time. - Conclusions Our results show that anticholinergic prescribing increases despite the deteriorating health status of older adults, which may lead to higher hospitalisation and mortality rates. New practice recommendations for general practitioners may be helpful in raising their awareness of cumulative ACB and enabling them to discontinue or reduce the dose of some anticholinergics where possible. However, further research is needed to assess the impact of our findings on prescribing behaviour in primary care. - Trial registration number ISRCTN89818205.
Online veröffentlicht: 3. Juni 2025
Gesehen am 11.09.2025